A curriculum-integrated sun safety intervention to improve adolescent skin health knowledge in an independent girls’ secondary school - Rachael S. Jefferson; Kelly M. Bentley-Spuur; Kenneth Chinkwo; Clare L. Singh; Simon Board; Philip L. Tong; Minh T. Chau (PLoS ONE, 2026)
Australia has one of the world’s highest melanoma incidences among youth. Adolescents often under-prioritise sun protection due to sociocultural factors, for example, the perceived attractiveness of tanned skin and a sense of invulnerability. This study reports on a curriculum-integrated sun safety intervention implemented in a single independent girls’ secondary school, a context that provides important insights but also limits generalisability to mixed-gender and other school settings. High school students (aged 13–15) participated in sun safety workshops integrated into their Personal Development, Health, and Physical Education (PDHPE) curriculum. Sun protection knowledge, attitudes toward tanning, and self-reported protective behaviours were assessed via surveys administered pre-intervention, immediately post-intervention, and five months later. Students’ sun safety knowledge increased significantly post-intervention (p < 0.001), and remained higher than baseline knowledge at 6 months, indicating substantial knowledge retention. Participants reported more frequent sunscreen use and protective behaviours after the program. The intervention also reduced the appeal of tanning, fewer students agreed that “a suntan looks good” after participating. Notably, all students regardless of ethnicity (Caucasian, Asian, Other), showed knowledge gains, but variations were observed. Students from historically underserved ethnic backgrounds started with lower baseline knowledge and exhibited slightly smaller improvements aligning with prior findings that sun awareness has differed across racial/ethnic group. These findings suggest that an engaging, curriculum-integrated sun safety program can produce immediate and sustained improvements in adolescents’ sun protection knowledge and attitudes within a girls’ secondary school context. While the single-site design limits broader generalisation, the results highlight the potential value of embedding sun safety education within school curricula. Future research should examine the effectiveness of this intervention across multiple school sites, including co-educational and diverse educational settings, to strengthen evidence for scalability and policy implementation aimed at long-term skin cancer prevention.